Masyarakat Era Kontemporer Dalam Menghadapi Risiko Plastik - Andina Arsy Hanifah; Alfatah Adi Nugroho; Ayudya Valentina Tunggadewi (Student Scientific Creativity Journal, 2023)
The presence of plastic in today's contemporary era, has various functions that greatly help people's lives. Plastic with all its properties, which are more inclined to the many advantages of its use and flexibility so that it is easy to use in various fields of life. With this fact, there are more and more products that rely on plastic as a basic ingredient in the manufacture of their products. This is of course supported by very high market demand, so that all types of production of goods made from plastic are mushrooming. If we return to our original purpose, the creation of plastic was indeed used as a substitute for paper bags, which at that time was experiencing a crisis of threats due to the increasing number of illegal logging incidents, so that there was a potential for the scarcity of the trees themselves. However, the opposite is currently true, where the use and production of plastics is increasingly dominating, making the remaining production waste and waste resulting from its use even more insurmountable. This is compounded by the fact that plastic is difficult to decompose, requiring hundreds of years of time. This, in the concept of a risk society is called the boomerang effect, because something that existed in the industrial era was created as a form of innovation that exists as a solution, but in the modern era like now it has become a separate risk for the surrounding community. For various phenomena as a result of the creation of plastic itself, society does not necessarily let them slowly be swallowed up by existing risks, but there are many efforts to create innovations as a way to protect themselves from various risks distributed by production and the increasingly widespread use of plastic in today's reality.